SMIMO Radar: MIMO Radar with Subarray Elements of Phased-Array Antenna - Syahfrizal Tahcfulloh (IJITEE (International Journal of Information Technology and Electrical Engineering), 2021)
Unlike Phased-MIMO Radar (PMIMO) which employs overlapping equal subarrays (OES) only on the transmit (Tx), Subarray-MIMO (SMIMO) radar utilizes the combination of subarrays, both in the transmit (Tx) and receive (Rx). SMIMO radar is MIMO radar with subarray elements acting as Phased-Array (PA). It simultaneously combines the primary advantages of PA and the MIMO radar; they are high directional gain and high diversity gain, respectively. High directional gain is beneficial to improve the range target, while high diversity gain is beneficial to improve the number of target detection. The use of the subarray methods in the Tx-Rx array could be configured such as in verlapping subarray (OS), non-overlapping subarray (NOS), equal subarray (ES), unequal subarray (US), and/or the combination of all configurations. Various configurations in Tr-Rx would determine the performance of radar, such as the number of virtual arrays, the maximum number of target detections, the detection accuracies, and the angular resolutions along with its effectivity compared to PA, MIMO, and Phased-MIMO radar. Numerical results and simulation showed that SMIMO provided higher flexibility than other radars by configuring Tx-Rx to easily adapt to various changes of target conditions and their surroundings.